The Attorney's Wiretapping Authority in Special Crimes and Military Crime Connection Cases - Wibisono, Danny K Wibisono; Hariyanti, Dilla; ., Mugiati (KnE Social Sciences, 2024)
The authority in lawful interception in the legal norms in force, in Indonesia today, can be exercised by Law Enforcement Officials (APH) and State Intelligence (IN). APH includes the Police, the Attorney General’s Office, the National Narcotics Agency, and the Corruption Eradication Commission, while the only state intelligence agency that has authority is the State Intelligence Agency. The Attorney General’s Office in accordance with legal norms has the authority to investigate general crimes in accordance with the material provisions of the Criminal Code (KUHP), special crimes according to provisions outside the Criminal Code, and military crimes in accordance with the provisions of military criminal law after the formation of the Junior Attorney General for Military Criminals ( Jampidmil). The Attorney General’s authority is to handle specific criminal acts related to corruption, gross human rights violations, money laundering, insubordination, use of unlawful force, theft, embezzlement, and other violations of law involving military personnel. This study will discuss the wiretapping authority of the Attorney General’s Office when dealing with special crimes, namely corruption and military crimes connected with terrorism so that the difference in wiretapping procedures can be seen in the handling of these two different crimes at the stages of investigation and prosecution. Keywords: attorney general, lawful interception, investigation, corruption, military crime